2002
DOI: 10.1111/j.1654-109x.2002.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in species composition of upland sown grassland under extensive grazing management

Abstract: Abstract. Due to economic pressures and policy changes Lolium perenne‐Trifolium repens sown swards in upland UK sheep systems are likely to become less intensively managed. We present results from the first 5 yr of a long‐term experiment studying vegetation change under more extensive grazing management at three sites. One treatment was representative of current, intensive management and 5 were unfertilized with different intensities of seasonal grazing. The species composition of unfertilized, ungrazed sward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…After a change in grazing intensity, species abundance changes more rapidly than plant species richness (Marriott et al, 2002;Louault et al, 2005;Scimone et al, 2007). However, we could not find any global effect of stocking rate on the Shannon index (F 1.30 5 0.06; P 5 0.81; Figure 3) or other indicators of plant community evenness (log normal diversity index: Bullock et al, 2001; Simpson dominance index: Scimone et al, 2007).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…After a change in grazing intensity, species abundance changes more rapidly than plant species richness (Marriott et al, 2002;Louault et al, 2005;Scimone et al, 2007). However, we could not find any global effect of stocking rate on the Shannon index (F 1.30 5 0.06; P 5 0.81; Figure 3) or other indicators of plant community evenness (log normal diversity index: Bullock et al, 2001; Simpson dominance index: Scimone et al, 2007).…”
Section: Resultsmentioning
confidence: 59%
“…Qualitative review indicated that grazing abandonment rapidly changed plant species composition over a wide range of plant communities, such as ryegrass/white clover sown swards (Marriott et al, 2002) or Lolium perenne-Agrostis capillaris-dominated pasture (Fothergill et al, 2002). Legumes dropped in abandoned grasslands (Dutoit et al, 1995;Gross et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grant et al 1996;Hulme et al 1999;Smith et al 2000b;Bullock et al 2001;Marriott et al 1998Marriott et al , 2002 in extensive systems. Fewer studies have looked at the effects of grazing on the soil.…”
Section: Introductionmentioning
confidence: 96%
“…This could best be achieved by establishing species-rich, low-input meadows, or by leaving off intensive management in existing grasslands (Szemán, 1997). In both cases considerable changes can be expected in the composition of the grassland, involving an increase in species richness (Marriott et al, 2002;2009). This is especially important on nature-protected grass areas and bio-grasslands and for the restoration of grasslands and habitats.…”
mentioning
confidence: 99%